Based Learning Method in Increasing Student Interaction and Interest in Islamic Religious Education Learning at SMAN 1 Woha - Alamsyah; Ruslan; Sri Jamilah (Lembaga Bale Literasi, 2026)
This study aims to examine the implementation of the Based Learning method in increasing student interaction and interest in learning Islamic Religious Education at SMAN 1 Woha. This research uses a qualitative approach, with data collected through interviews, observation, and documentation. The results of the study show that the application of the Based Learning method in Islamic Religious Education (PAI) learning shows significant effectiveness in increasing interaction and interest in learning. Through this approach, students are confronted with contextual problems related to everyday life, thus encouraging them to gain a deeper and more applicable understanding of Islamic Religious Education (PAI) material. Furthermore, Based Learning also contributes to strengthening students' social skills, such as communication and group collaboration , and increasing their sensitivity to social issues in their surroundings, particularly by enhancing interaction and learning interest.